The transcriptomic and evolutionary signature of social interactions regulating honey bee caste development. Issue 21 (8th October 2015) - Vojvodic, Svjetlana; Johnson, Brian R.; Harpur, Brock A.; Kent, Clement F.; Zayed, Amro; Anderson, Kirk E.; Linksvayer, Timothy A.
Abstract: The caste fate of developing female honey bee larvae is strictly socially regulated by adult nurse workers. As a result of this social regulation, nurse‐expressed genes as well as larval‐expressed genes may affect caste expression and evolution. We used a novel transcriptomic approach to identify genes with putative direct and indirect effects on honey bee caste development, and we subsequently studied the relative rates of molecular evolution at these caste‐associated genes. We experimentally induced the production of new queens by removing the current colony queen, and we used RNA sequencing to study the gene expression profiles of both developing larvae and their caregiving nurses before and after queen removal. By comparing the gene expression profiles of queen‐destined versus worker‐destined larvae as well as nurses observed feeding these two types of larvae, we identified larval and nurse genes associated with caste development. Of 950 differentially expressed genes associated with caste, 82% were expressed in larvae with putative direct effects on larval caste, and 18% were expressed in nurses with putative indirect effects on caste. Estimated selection coefficients suggest that both nurse and larval genes putatively associated with caste are rapidly evolving, especially those genes associated with worker development. Altogether, our results suggest that indirect effect genes play important roles in both the expression and evolution of socially influenced traits such as caste. Abstract : RNA sequencing identified genes expressed in both developing honey bee larvae and their care‐giving nurses that are associated with larval caste fate. Genes associated with caste were rapidly evolving, especially those associated with worker development.